Designing and assessment of accuracy of an algorithm for determining the accuracy of radiographic film density by changing exposure time - Hoorieh Bashizadeh Fakhar; Elham Sadat Emadian Razavi (Tehran University of Medical Sciences, 2014)
Background and Aims Bone density is frequently used in medical diagnosis and research. The current methods for determining bone density are expensive and not easily available in dental clinics. The aim of this study was to design and evaluate the accuracy of a digital method for hard tissue densitometry which could be applied on personal computers.   Materials and Methods: An aluminum step wedge was constructed. 50 E-speed Kodak films were exposed. Exposure time varied from 0.05s to 0.5 s with 0.05 s interval. Films were developed with automatic developer and fixer and digitized with 1240U photo Epson scanner. Images were cropped at 10 × 10mm size with Microsoft Office Picture Manager. By running the algorithm designed in MATLAB software, the mean pixel value of pictures was calculated.   Results: Finding of this study showed that by increasing the exposure time, the mean pixel value was decreased and at step 12, a significant discrimination was seen between the two subsequent times(P<0.001). By increasing the thickness of object, algorithm could define the density changes from step 4 in 0.3 s and 5 in 0.5 s, and it could determine the differences in the mean pixel value between the same steps of 0.3 s and 0.5 s from step 4.   Conclusion: By increasing the object thickness and exposure time, the accuracy of the algorithm for recognizing changes in density was increased. This software was able to determine the radiographic density changes of aluminum step wedge with at least 4mm thickness at exposure time of 0.3 s and 5 mm at 0.5 s.